Pengetahuan WUS tentang Akupresure Mengatasi Mual Muntah pada Ibu Hamil di RT 09 RW 05 Kelurahan Langensari - Rully Atia Wijaya; Wahyu Kristiningrum; Maria Emensia Ero Ruing; Ria Ma’rifah (Universitas Ngudi Waluyo, 2022)
Nausea and vomiting is a symptom that often occurs in the first trimester of pregnancy. Nausea occurs in the morning, but can occur at any time and at night. These symptoms occur approximately 6 weeks after the first day of the last menstrual period and last for approximately 10 weeks.This condition can be overcome with acupressure so as to suppress the occurrence of complications in the mother and fetus. The results of the family assessment in RT 09 RW 09 found 2 pregnant women who experienced nausea and vomiting. In connection with this problem, the community service program, especially in RT 09 RW 05, Langensari Village, provides a solution to this problem by conducting Health Promotion activities about acupressure at 13 WUS. The purpose of this activity is to increase WUS knowledge about acupressure to reduce nausea and vomiting. The results of this activity indicate that WUS knowledge increases after Health Promotion is carried out. Health promotion activities regarding acupressure to reduce nausea and vomiting were carried out on May 23, 2022 at the residence of RT 09 RW 05. The primary target of this activity is WUS. The activity was carried out through 3 stages, namely the preparation, implementation and evaluation stages. The results of the activity showed that before being given health promotion about acupressure to reduce nausea and vomiting in pregnant women the distribution of values from 13 WUS RT 09 RW 05 most of them had less knowledge as much as 11 WUS (86.6%) and 2 WUS (15.4) had sufficient knowledge. %). After being given health promotion about acupressure to reduce nausea and vomiting in pregnant women, the distribution of values from 13 WUS RT 09 RW 05 mostly had good knowledge of 13 people (100%). This shows that there is an increase in WUS knowledge after being given health promotion. AbstrakMual muntah adalah gejala yang sering terjadi pada kehamilan trimester I. Mual terjadi pada pagi hari, tetapi dapat timbul setiap saat dan malam hari gejala-gejala ini terjadi kurang lebih 6 minggu setelah hari pertama haid terakhir dan berlangsung selama kurang lebih 10 minggu. Kondisi ini dapat diatasi dengan akupresure sehingga menekan terjadinya komplikasi pada ibu dan janin. Hasil pengkajian keluarga di RT 09 RW 05 Kelurahan Langensari dari 13 wanita usia subur terdapat 2 ibu hamil yang mengalami mual muntah. Berkaitan dengan masalah tersebut, program pengabdian masyarakat di RT 09 RW 05 Kelurahan Langensari memberi solusi untuk permasalahan mual muntah pada ibu hamil dengan melaksanakan kegiatan Promosi Kesehatan tentang akupresure untuk mengatasi mual muntah. Tujuan dari kegiatan ini adalah meningkatkan pengetahuan WUS tentang akupresure untuk mengurangi mual muntah. Kegiatan promosi kesehatan tentang akupresure untuk mengurangi mual muntah dilaksanakan pada tanggal 23 Mei 2022 di rumah Bapak Suparno sebagai Ketua RT 09 RW 05, dihadiri oleh 13 WUS. Sasaran Primer kegiatan ini adalah WUS. Kegiatan dilakukan melalui 3 tahap yaitu tahap persiapan, pelaksanaan dan evaluasi. Hasil kegiatan diketahui bahwa sebelum diberi promosi kesehatan tentang akupresure untuk mengurangi mual muntah pada ibu hamil distribusi nilai dari 13 WUS RT 09 RW 05 sebagian besar memiliki pengetahuan kurang, sebanyak 11 WUS (86,6%) dan berpengetahuan cukup, sebanyak 2 WUS (15,4%). Kemudian setelah diberikan promosi kesehatan tentang akupresure untuk mengurangi mual muntah pada ibu hamil distribusi nilai dari 13 WUS RT 09 RW 05 sebagian besar memiliki pengetahuan baik sebanyak 13 orang (100%). Hal ini menunjukan bahwa terdapat peningkatan pengetahuan WUS setelah diberi promosi Kesehatan.